Bone Marrow Cellular Therapies: Novel Therapy for Knee Osteoarthritis - Piuzzi, Nicolas S.; Khlopas, Anton; Newman, Jared M.; Ng, Mitchell; Roche, Martin; Husni, M. Elaine; Spindler, Kurt P.; Mont, Michael A.; Muschler, George (The Journal of Knee Surgery, 2018)
Cellular therapies are emerging as potentially promising treatments for numerous musculoskeletal conditions, such as knee osteoarthritis (OA). As orthopaedic surgeons represent a sizable portion of the providers who deliver these therapies, it is particularly essential for them to understand their fundamental principles. One major principle is to identify the appropriate sources for obtaining these cells, with bone marrow being most common. Therefore, the purpose of this review was to provide an overview of cell-based therapies available for the treatment of knee OA with a focus on bone marrow-derived cellular therapies. Specifically, we discuss (1) bone marrow aspiration technique, (2) processing to bone marrow aspirate concentrate, and (3) the rational and clinical evidence for the use of bone marrow cellular therapies for the treatment of knee OA.
Keywords: cell therapies; knee osteoarthritis; bone marrow cellular therapies; bone marrow